Supply Chain Risk Assessment and Mitigation in Sugar Industry - Sinta Dewi; Rr. Rochmoeljati; Chori Dwi Azizah; Christabela Jesselyn (Nusantara Science and Technology Proceedings, 2023)
In the fulfillment of consumer needs, companies can experience several risks. To overcome possible risks, companies must be able to manage the supply chain effectively. The sugar industry has a complex supply chain, and at each stage of the supply chain, some risks must be taken into account. The purpose of this study is to determine the risks that may occur and prioritize risk mitigation strategies to minimize existing risks. This study uses the House of Risk method. From the results of House of Risk Stage 2, 13 risk mitigation actions were obtained to propose solutions to minimize the occurrence of risk agents.